2008
DOI: 10.2139/ssrn.1119318
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, Inflation and Exchange Rate Regimes in Small Open Economies

Abstract: Remittances are private monetary transfers. Yet the rapidly growing literature on the subject often ignores the role that exchange rate regimes play in determining the effect remittances have on a recipient economy. This paper uses a theoretical model and panel vector autoregression techniques to explore the role exchange rate regimes play in understanding the effect of remittances. The analysis considers yearly and quarterly data for seven Latin American countries. Our theoretical model predicts that remittan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…The present result contradicts those of Buch and Kuckulenz (), Efobi et al () and Ball et al . (), who argue that remittances generate no change in the money supply and decrease the general price level. Although Buch and Kuckulenz reported the impact of domestic inflation on remittances to be negative, they did not find a strong correlation between the two.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…The present result contradicts those of Buch and Kuckulenz (), Efobi et al () and Ball et al . (), who argue that remittances generate no change in the money supply and decrease the general price level. Although Buch and Kuckulenz reported the impact of domestic inflation on remittances to be negative, they did not find a strong correlation between the two.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…We then derive the impulse response functions from equation (1) relying on the Cholesky decomposition to orthogonalize the residuals. For this purpose, "the variables must be ordered such that variables placed higher in the ordering have a contemporaneous impact on all variables lower in the ordering" (Ball et al, 2009). Hence, the first variables should be the most exogenous.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, their findings suggest that these effects operate stronger under fixed exchange rate regimes. Ball et al (2013) analyze the short-run dynamics triggered by an increase in remittances under different exchange rate regimes, with a focus on the monetary nature of remittances. The theoretical predictions indicate that under a fixed exchange rate regime, a rise in remittances leads to an increase in GDP, increase in the rate of inflation and an appreciation of the real exchange rate, while under a flexible exchange rate regime they generate an increase in GDP, an appreciation of the real exchange rate, but a decrease in inflation rate.…”
Section: Related Literaturementioning
confidence: 99%
“…The main mechanism through which this can occur is the well-known Dutch disease phenomenon. Studies on such short-run dynamics, in general, have found that flexible exchange rate regimes tend to minimize the inflationary consequences of the inflow of remittances (Ball et al, 2013). A supporting argument is that in the case where monetary policy EXCHANGE RATE REGIMES, REMITTANCES AND GROWTH is not devoted to pegging the nominal exchange rate, an inflation targeting regime, for instance, generates dynamics that lead to lower nontradable inflation and a favorable outcome for the tradable sector that is considered key to economic growth (Lartey, 2015).…”
Section: Policy Implicationmentioning
confidence: 99%